Comparison of avian Chlamydia psittaci isolates by restriction endonuclease analysis and serovar-specific monoclonal antibodies. - Andersen, A A (1991)
Avian Chlamydia psittaci isolates were examined by restriction endonuclease analysis and serovar-specific monoclonal antibodies and compared with ovine abortion and polyarthritis isolates. The avian isolates were divided into four serovars (turkey, psittacine, pigeon, and duck) based on their reactivity to the monoclonal antibodies. The DNA digest patterns were similar across the four avian serovars; most bands were identical when the isolates were tested with PstI, BamHI, and EcoRI restriction endonuclease enzymes. The turkey group restriction endonuclease analysis patterns were distinguished from those of the other avian strains by three to four band differences with all enzymes. The duck and pigeon isolates showed only minor DNA pattern differences when compared with the psittacine isolates. Four psittacine isolates from various locations in Texas had an extra band with the EcoRI restriction enzyme, suggesting that they were from a common source; however, they were indistinguishable from the other psittacine isolates when examined with the monoclonal antibodies. The avian isolates were distinctly different from either abortion or polyarthritis isolates by both restriction endonuclease analysis and monoclonal antibody analysis. The data demonstrate that the avian isolates form a distinct group or separate biovar with at least four serovars.